Gaming Tree Based Evaluation Model for Badminton Tactic Benefit Analysis and Prediction - Wenming Liu; Yifan Zhu; Wenxia Guo; Xinyuan Wang; Songkun Yu (Applied Sciences, 2023)
Badminton tactics refer to the techniques and strategies employed by players to win a match. Analyzing these tactics can help players improve their performance and outsmart their opponents. To study the tactics of top players, we use a gaming tree to analyze matches between two of the most powerful badminton players in history: Lin and Lee. By employing the Nash Equilibrium, we can discover the most beneficial strategies for both players, which reflect their most powerful techniques. Additionally, with the help of this gaming tree, we can precisely predict how players will implement their tactics. Empirical experimental results demonstrate that our proposed method not only evaluates and identifies each player’s weaknesses and strengths but also has powerful capabilities to predict their tactics.